How an overweight and rapidly rotating PG 1159 star in the Galactic halo challenges evolutionary models - Mackensen, Nina; Reindl, Nicole; Werner, Klaus; Dorsch, Matti; Tan, Shuyu (Astronomy and astrophysics, 2025)
PG 1159 stars are thought to be progenitors of the majority of H-deficient white dwarfs. Their unusual He-, C-, and O-dominated surface composition is typically believed to result from a late thermal pulse experienced by a single (pre-)white dwarf. Yet other formation channels - involving close binary evolution - have recently been proposed and could lead to similar surface compositions. Here we present a non-local thermodynamic equilibrium spectral analysis based on new UV and archival optical spectra of one of the hottest PG 1159 stars, RX J0122.9-7521. We find Teff = 175 kK and log g = 7.7, and an astonishingly low O/C ratio of 7.3 × 10−3 (by mass). By combining the spectroscopic surface gravity and Gaia parallax with a spectral energy distribution fit, we derive a mass of Mspec = 1.8−0.7+1.1 M⊙. Although this spectroscopic mass is higher than predicted by evolutionary models, it is subject to substantial uncertainty. Furthermore, we find that RX J0122.9-7521 shows strongly rotationally broadened lines, suggesting that the previously reported photometric period of 41 min indeed corresponds to the rotational period of this star. Our kinematic analysis shows that RX J0122.9-7521 belongs to the Galactic halo, which - assuming single-star evolution - is in stark contrast to its relatively high mass. The rapid rotation, high mass, and halo kinematics, as well as the lack of evidence of a close companion, led us to the belief that RX J0122.9-7521 formed through the merger of two white dwarfs. Yet, none of the current models can explain the surface abundances of RX J0122.9-7521.
Online veröffentlicht: 29. Juli 2025
Gesehen am 13.01.2026